Saberes tradicionais da Comunidade Quilombola de Vão das Palmeiras, Seabra-Ba: uma abordagem da cultura fumageira - Jesus, Edicacio Souza de (2025)
The Quilombola Community of Vão das Palmeiras, located in the municipality of Seabra, in the Chapada Diamantina region of Bahia, stands out for its cultural, historical, and environmental relevance. This participatory research, based on a qualitative approach and exploratory technique, had as its main objective to investigate the community’s traditional knowledge, which resulted in a greater focus on tobacco cultivation, as this crop remains an important income-generating strategy in Vão das Palmeiras. During the diagnostic stage, observations were conducted, questionnaires were administered, and both conversation circles and individual semi-structured interviews were carried out with local residents, using the network sampling technique, also known as “snowball sampling.” Thus, the participants who were initially interviewed indicated other community members to take part in the research. For data analysis, the Content Analysis technique was employed in order to understand the participants’ perceptions. The content was examined in detail, allowing the results to be organized into five categories: main agricultural crops, productive practices, economic aspects, agricultural memory and tradition, as well as policies and social impacts. The research findings revealed that, despite the reduction in consumption and anti-smoking policies, tobacco remains both a source of income and a practice of cultural and identity relevance, transmitted across generations. The agricultural practices observed showed a predominance of organic fertilizers and traditional techniques of soil preparation, harvesting, and tobacco curing, still marked by collective labor and the intergenerational transmission of knowledge. Among the challenges identified were scarce rainfall and pests, especially caterpillars, which were recognized as limitations to productive viability. Cultural and religious practices were also recorded, such as the Terno de Reis celebration and the use of medicinal plants, reaffirming the community’s identity and way of life. The results supported the production of a documentary entitled “Traditional Knowledge of the Quilombola Community of Vão das Palmeiras, Seabra-BA: An Approach to Tobacco Culture,” developed as part of this research. The documentary made it possible to document and value this traditional knowledge, while also reinforcing the participatory nature of the study. In this way, the research not only achieved its objectives but also contributed to the preservation of collective memory, strengthening cultural identity and promoting recognition of the traditional knowledge of Vão das Palmeiras.